Gravity feed water treatment system - Conrad, Kenneth E; Beals, Brian S; Taylor, Jr., Roy M; Stoner, Jr., William T; Lautzenheiser, Terry L; Schamper, Ryan D; VanderKooi, Karen J; Kuennen, Roy W (2019)
A portable water treatment system includes at least one sub-system to treat water including a flocculation system, a chlorination system, and a bio-sand filter system. The water treatment system may include multiple sub-systems for treating water that feed into one another. The sand filter system may include a mini bio-sand filter, a foam filter, or a pressed block filter. The flocculation system may include a tank bottom that urges settling particles toward a sump and a ladle that removes settled particles. A manual pump or siphon may be included in the water treatment system.